La politique étrangère : État des travaux scientifiques - Donneur, André; Beylerian, Onnig (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
Theoretical studies of foreign policy show that the very subject of the discipline is highly undefined. This is the reason why we shall try, first and foremost, to provide an answer to three fundamental questions. Is there a natural difference between foreign policy and decision-making, or is foreign policy only a sum total of decisions? Is there a difference between a foreign policy which dictates the major general trends and the various policies which apply to restricted scenes of action ? What is the difference between the objectives which actors assign to various policies and their implementation in the international System, thus making their evaluation a problem ? We then deal with the state of studies entered upon by three schools of thought and set down the results registered by the behaviorist trend, the theoretical dilemma it had to face and the dead end it led to. The second trend, historical and political, has, for its part, dealt with comparative analysis of historical cases according to the method of localized and structured comparison. Finally, the third trend, historical, economical and structuralist, has resorted to the world System paradigm of I. Wallerstein. The problem of this paradigm is the transposition of the debate between the supporters of the Annales school (structural serial history, economical and social contingencies) and the historians of international relations (who favour history of events and the role of the state). This approach also focuses on the debate about the dichotomy international relations/transnational relations. In the ends, rigorous and interdisciplinary research studies is deemed necessary for the promotion of studies in foreign policy.